COVID-19 stressors for Hispanic/Latino patients living with type 2 diabetes: a qualitative study - Williams, Myia S.; Cigaran, Edgardo; Martinez, Sabrina; Marino, Jose; Barbero, Paulina; Myers, Alyson K.; DiClemente, Ralph J.; Goris, Nicole; Gomez, Valeria Correa; Granville, Dilcia; Guzman, Josephine; Harris, Yael T.; et al. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background and aim: During the early stages of the COVID-19 pandemic, nationwide lockdowns caused disruption in the diet, physical activities, and lifestyle of patients with type 2 diabetes. Previous reports on the possible association between race/ethnicity, COVID-19, and mortality have shown that Hispanic/Latino patients with type 2 diabetes who are socio-economically disadvantaged are most disproportionality affected by this novel virus. The aim of this study was to explore stressors associated with changes in diabetes self-management behaviors. Our goal is to highlight the health disparities in these vulnerable racial/ethnic minority communities and underscore the need for effective interventions. Methods and participants: Participants were enrolled in part of a larger randomized controlled trial to compare Diabetes Telehealth Management (DTM) to Comprehensive Outpatient Management (COM) on critical patient-centered outcomes for Hispanic/Latino patients with type 2 diabetes. We conducted a thematic analysis using patient notes collected from two research nurses between March 2020 and March 2021. Two authors read through the transcripts independently to identify overarching themes that emerged. Once identified, both authors convened to compare themes and ensure similar themes were identified within the transcripts. Any discrepancies were discussed by the larger study team until a consensus was reached. Results: Six themes emerged which are further delineated as sources of stress and subsequent outcomes. Namely, sources of stress associated with the COVID-19 Pandemic: (1) Fear of contracting COVID-19, (2) Disruptions from lockdowns, (3) Financial stressors (e.g. loss of income); and Outcomes of COVID-19 stressors: (1) Reduced diabetes management (e.g. reduced diabetes monitoring and physical activity), (2) Suboptimal mental health outcomes (e.g. anxiety and depression), (3) outcomes of financial stressors. Conclusion: Findings indicate that under-served Hispanic/Latino patients with type 2 diabetes encountered a number of stressors that deteriorated diabetes self-management behaviors during the pandemic.